The role of sperm DNA fragmentation testing in predicting intra-uterine insemination outcome: A systematic review and meta-analysis. (January 2020) - Sugihara, Alessa; Van Avermaete, Freya; Roelant, Ella; Punjabi, Usha; De Neubourg, Diane
Abstract: There is a growing body of literature that recognizes the importance of sperm DNA fragmentation as a candidate test for the assessment of sperm function and thus male reproductive potential. Research on the subject has mostly been focused on couples undergoing IVF/ICSI treatment whilst much uncertainty still exists about the relationship between sperm DNA fragmentation and IUI. This study systematically reviews the literature, aiming to define the value of sperm DNA fragmentation measurement in predicting clinical pregnancy outcome in couples undergoing intra-uterine insemination From inception until March 2018, the relevant databases were searched for studies investigating the relationship between sperm DNA fragmentation as measured by SCSA, TUNEL, SCD or Comet assay and pregnancy outcome after IUI. The Quality in Prognosis Studies (QUIPS) tool was utilized for quality assessment. This review is reported according to the 2009 PRISMA statement. The literature search resulted in 433 studies of which we finally retained nine studies for the qualitative analysis and four studies for the meta-analysis, accounting for 940 IUI cycles. In summary, the observed effect of low sperm DNA fragmentation on clinical pregnancy after IUI as analyzed with the random effects model reveals a relative risk of 3.15 (95% CI: 1.46–6.79; I2 = 13.1%) and pooled sensitivity and specificity of respectively 94% (95% CI: 0.88; 0.97) and 19% (95% CI: 0.14; 0.26). Taken together, the included studies show a limited capacity of sperm DNA fragmentation in discriminating between couples who will benefit from the test, namely in either predicting IUI outcome or in advising for or against IUI as first choice of treatment instead of advancing to more invasive medically assisted reproduction. This review has thrown up many questions in need of further investigation. As such, future studies might explore issues such as determining relevant cut-off values for prediction of spontaneous pregnancy and pregnancy after IUI as well as the assessment of the stability of the test over time and before and after density gradient centrifugation.